Cardiac dysfunction and peri-weaning mortality in malonyl-coenzyme A decarboxylase (MCD) knockout mice as a consequence of restricting substrate plasticity. - Aksentijević, D; McAndrew, D; Karlstädt, A; Zervou, S; Sebag-Montefiore, L; Cross, R; Douglas, G; Regitz-Zagrosek, V; Lopaschuk, G; Neubauer, S; Lygate, C (Academic Press, 2014)
UNLABELLED: Inhibition of malonyl-coenzyme A decarboxylase (MCD) shifts metabolism from fatty acid towards glucose oxidation, which has therapeutic potential for obesity and myocardial ischemic injury. However, ~40% of patients with MCD deficiency are diagnosed with cardiomyopathy during infancy. AIM: To clarify the link between MCD deficiency and cardiac dysfunction in early life and to determine the contributing systemic and cardiac metabolic perturbations. METHODS AND RESULTS: MCD knockout mice ((-/-)) exhibited non-Mendelian genotype ratios (31% fewer MCD(-/-)) with deaths clustered around weaning. Immediately prior to weaning (18days) MCD(-/-) mice had lower body weights, elevated body fat, hepatic steatosis and glycogen depletion compared to wild-type littermates. MCD(-/-) plasma was hyperketonemic, hyperlipidemic, had 60% lower lactate levels and markers of cellular damage were elevated. MCD(-/-) hearts exhibited hypertrophy, impaired ejection fraction and were energetically compromised (32% lower total adenine nucleotide pool). However differences between WT and MCD(-/-) converged with age, suggesting that, in surviving MCD(-/-) mice, early cardiac dysfunction resolves over time. These observations were corroborated by in silico modelling of cardiomyocyte metabolism, which indicated improvement of the MCD(-/-) metabolic phenotype and improved cardiac efficiency when switched from a high-fat diet (representative of suckling) to a standard post-weaning diet, independent of any developmental changes. CONCLUSIONS: MCD(-/-) mice consistently exhibited cardiac dysfunction and severe metabolic perturbations while on a high-fat, low carbohydrate diet of maternal milk and these gradually resolved post-weaning. This suggests that dysfunction is a common feature of MCD deficiency during early development, but that severity is dependent on composition of dietary substrates.